Primary Leiomyosarcoma of the Glans - Costa Junior, Raimundo Nonato Gois da; Teixeira Júnior, Antonio Augusto Lima; Rocha, Thalita Moura Silva; Sobrinho, Thaís Bastos Moraes; Barbosa, Liseana de Oliveira; Silva, Rafael Campos; Corrêa, Rita da Graça Carvalhal Frazão; Alencar Junior, Antonio Machado; Nascimento, Francisco Sergio Moura Silva; Melo, Syomara Pereira da Costa; Calixto, José Ribamar Rodrigues; Silva, Gyl Eanes Barros (Frontiers in Oncology, 2022)
Penile leiomyosarcoma is an extremely uncommon entity that rarely occurs in the glans. Due to the limited number of cases described in literature, guidelines regarding non-surgical treatment, prognosis, and management remain equivocal. Among the mesenchymal tumors of the penis, leiomyosarcoma has the highest propensity for recurrence. It originates in the smooth muscle cells from two distinct locations: superficial and deep. The deep subtype is the most aggressive and has the highest potential for metastasis. Surgical treatment should be implemented early and must be locally aggressive. Herein, we present a rare case of a 54-year-old patient with deep localized leiomyosarcoma of the glans, albeit with superficial characteristics. A review of the main histopathological, clinical, immunohistochemical, and therapeutic aspects of this unusual entity is presented.